Inheritance Law in Minangkabau: A Comparative Study of the Application of Islamic and Customary Inheritance Law in Koto Tangah Subdistrict and Nanggalo Padang City: (Hukum Waris di Minangkabau: Studi Komparatif Penerapan Hukum Waris Islam dan Adat di Kec. Koto Tangah dan Nanggalo Kota Padang) - Rahmadanil, Rahmadanil; Zuwanda, Rifka (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2021)
Abstract: Inheritance, according to Minangkabau custom, is given to girls, not boys. In Islam, property inheritance is regulated by Far?i? fiqh, which gives to daughters, sons, spouses of heirs (husband or wife) and even the inheritor's parents. Property inherited from generation to generation in the Minangkabau community is called